Efficacy and safety of gut microbiome-targeted treatment in patients with depression: a systematic review and meta-analysis - Bo Pan; Yiming Pan; Yu-Song Huang; Meng Yi; Yuwei Hu; Xiaoyu Lian; Hui-Zhong Shi; Mingwei Wang; Guifen Xiang; Wen-Yi Yang; Zhong Liu; Fangfang Xia (BMC Psychiatry)
Abstract Background The study aimed to comprehensively analyze and establish a framework for evaluating the efficacy of microbiome–targeted treatment (MTT) for depression. Methods We searched PubMed, Embase, Cochrane Library, Web of Science, and the Chinese National Knowledge Infrastructure database for randomized controlled trials (RCTs) on MTT in treating depression until October 19, 2023. A meta-analysis was conducted to evaluate the efficacy and safety of MTT. Comprehensive subgroup analyses were undertaken to explore factors influencing MTT’s efficacy in treating depression. This study was registered with PROSPERO (CRD42023483649). Results The study selection process identified 51,570 studies, of which 34 met the inclusion criteria. The overall pooled estimates showed that MTT significantly improved depression symptoms (SMD −0.26, 95% CI [−0.32, −0.19], I 2  = 54%) with acceptable safety. Subgroup analyses by geography showed that effectiveness was demonstrated in Asia (SMD −0.46, 95% CI [−0.56, −0.36], I 2  = 36%), while no evidence of effectiveness was found in Europe (SMD −0.07, 95% CI [−0.19, 0.05], I 2  = 55%), America (SMD −0.33, 95% CI [−0.67, 0.02], I 2  = 60%), and Oceania (SMD 0.00, 95% CI [−0.18, 0.18], I 2  = 0%). Besides, the efficacy was shown in depressed patients without comorbidities (SMD −0.31, 95% CI [−0.40, −0.22], I 2  = 0%), whereas effectiveness was poor in those with digestive disorders, such as irritable bowel syndrome (SMD −0.37, 95% CI [−0.89, 0.16], I 2  = 74%), chronic diarrhea (SMD −0.34, 95% CI [−0.73, 0.05]), and chronic constipation (SMD −0.23, 95% CI [−0.57, 0.11], I 2  = 0%). In perinatal depressed patients, MTT was not effective (SMD 0.16, 95% CI [0.01, 0.31], I 2  = 0%). It was found that < 8 weeks (SMD −0.33, 95% CI [−0.45, −0.22], I 2  = 0%) and 8–12 weeks (SMD −0.34, 95% CI [−0.44, −0.23], I 2  = 57%) MTT were effective, while > 12 weeks (SMD 0.02, 95% CI [−0.12, 0.17], I 2  = 68%) MTT was ineffective. Conclusions Despite the overall effectiveness of MTT in treating depression and its acceptable safety profile, caution is warranted in drawing this conclusion due to limitations posed by the small sample size of included studies and heterogeneity. The efficacy of MTT for depression exhibits variation influenced by geography, patient comorbidities, and duration of administration.